2021
DOI: 10.1002/pro.4130
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol‐solubility alters amyloid fibril formation of α‐synuclein

Abstract: Amyloid fibril formation is associated with various amyloidoses, including neurodegenerative diseases such as Alzheimer's and Parkinson's diseases. Amyloid fibrils form above the solubility of amyloidogenic proteins or peptides upon breaking supersaturation, followed by a nucleation and elongation mechanism, which is similar to the crystallization of solutes. Many additives, including salts, detergents, and natural compounds, promote or inhibit amyloid formation. However, the underlying mechanisms of the oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…It should be noted that the solubility of polyphenols, in particular, KMP could alter their effects on the formation of amyloid fibrils. For instance, So et al (2021) evaluated the effects of KMP‐7─O─glycoside on the amyloid formation of α‐synuclein (αSN). They reported that the formation of amyloid is substantially increased following interactions of insoluble KMP‐7─O─glycoside with αSN (So et al, 2021).…”
Section: Kmp Modulates Aβ‐induced Toxicity In Admentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the solubility of polyphenols, in particular, KMP could alter their effects on the formation of amyloid fibrils. For instance, So et al (2021) evaluated the effects of KMP‐7─O─glycoside on the amyloid formation of α‐synuclein (αSN). They reported that the formation of amyloid is substantially increased following interactions of insoluble KMP‐7─O─glycoside with αSN (So et al, 2021).…”
Section: Kmp Modulates Aβ‐induced Toxicity In Admentioning
confidence: 99%
“…For instance, So et al (2021) evaluated the effects of KMP‐7─O─glycoside on the amyloid formation of α‐synuclein (αSN). They reported that the formation of amyloid is substantially increased following interactions of insoluble KMP‐7─O─glycoside with αSN (So et al, 2021).…”
Section: Kmp Modulates Aβ‐induced Toxicity In Admentioning
confidence: 99%
“…In this study, RLS was used to test the antiaggregation effect of CTZ against the fibrillation of HEWL by measuring fluorescence at 350 nm [ 27 ]. HEWL was incubated at pH 2.0, 55 °C, and 600 rpm for 10 h to induce amyloid fibrillation.…”
Section: Resultsmentioning
confidence: 99%
“…A cosolute-dependent change in the solubility model has been reported in recent years. In this model, hydrophobic compounds protect proteins from interactions with aqueous solutions and promote protein prescription, which may lead to increased aggregation [ 27 , 55 ]. Soluble aggregates are expected to be the main components of this prescription because of the lack of change in Thioflavin-T fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the concentration of free drugs in the plasma decreased quickly while drugs in the nanosystem stayed significantly longer in the plasma [ 96 ]. Kaempferol, a polyphenolic compound with antitumor activity, also faces the challenge of poor solubility [ 97 , 98 ]. A recent study reported a nanosystem incorporated with kaempferol that had excellent antitumor efficacy via disrupting calcium homeostasis in cancer cells [ 99 ].…”
Section: Advantages Of Nano-based Delivery Systems For Polyphenolic C...mentioning
confidence: 99%